Studies of the Homalomeneae (Araceae) of Peninsular Malaysia VII: Homalomena puncticulosa [Chamaecladon Clade], a new species from recreational forest - Sin Yeng, Wong; Boyce, Peter C. (Firenze University Press, 2021)
Homalomena puncticulosa is described and illustrated as a new species of the Chamaecladon Clade known from a single population in Selangor, and compared with the super-cially similar H. kiahii Furtado, and other similar Sumateran species.